Is there a new meaning of work? The how and why of a change in altruistic work values in Germany between 1989 and 2016 - Brinck, Karla Louise; Hauff, Sven; Kirchner, Stefan (management revue, 2020)
This study complements the discussion on changes in work values by insights about the dimension of altruistic work values, which to date has been largely neglected. In particular, we analyze how a change in the structure of the workforce (gender, age, and generation) has affected the importance of altruistic work values in the past decades. Using German data from four different years (1989, 1997, 2006, and 2016), we found that work values' importance has increased during the observed periods, while extrinsic work values have become less important and intrinsic work values have not changed. An increase of women and an aging workforce marginally have contributed to a change in altruistic work values, while shifting generational distribution had no effect. Overall, the explanatory powers of the included determinants are, despite their importance in theoretical discussions, fairly small. Thus, we discuss alternatives for explaining the change in altruistic work values.
CRIS-Team Scopus Importer:2025-04-09
Keywords: Aging workforce; Altruistic work values; Gender differences; Generation; Work values